Using Media (Video) to Improve Students’ Speaking Skill in Study Case: Junior High School - Nuriyanti, Ika (Indonesian Journal Publisher, 2024)
Learning media in the digital era must be aligned with technological developments. The learning media chosen must be interesting and attached to students. The video is currently popular with many people, including the students of Junior High School, MTsN 1 Kolpajung Pamekasan. Departing from these reasons, the researchers took the initiative to implement the video as a media for interesting and fun learning in delivering material in English for Junior High School. This study aims to find out how effective the video as media is in improving the speaking skills of students majoring at the MTsN 1 Kolpajung Pamekasan. Qualitative method is used for analyzing the data on performance test, observation and discussion on the implementation that were produced by the students as well as processing on student views regarding the use of video media in learning in English subject especially speaking skill. The result indicated that the use of video media is considered quite effective in developing students' speaking skills. From the results of observations, it shows that there has been an increase in student activity, from an average of 74.7% in cycle one and 82.2% in cycle two, to 86.3 in cycle III, as well as teacher activity in the learning process increasing from 85.7 % in cycle I, 90.3% in cycle II increased to 92.03% in cycle III which stated that video media was an innovation in learning English, which made students more relaxed and enjoyed the teaching and learning process and eliminated the mindset that learning English is difficult.